THE INFLUENCE OF BRAND IMAGE AND BRAND TRUST ON UNIQLO BRAND LOYALTY IN THE 2019 BATCH OF MANAGEMENT STUDENTS OF BUANA PERJUANGAN KARAWANG UNIVERSITY - Sobari, Obay; Isyanto, Puji; Sumarni, Neni (Universitas PGRI Semarang, 2024)
This research aims to investigate the impact of brand image and brand trust on brand loyalty. The approach used in this research is quantitative. The population of this research is Management students Class of 2019 who have purchased Uniqlo products, with a sample size of 92 respondents using a saturated sample. Primary data was obtained through distributing questionnaires to respondents. Data analysis was carried out using multiple linear regression analysis using SPSS version 25 software. The research results showed that brand image and brand trust both had a partially positive and significant influence on brand loyalty. And brand image and brand trust have a positive and significant influence simultaneously on brand loyalty. It is hoped that future researchers can add additional variables which theoretically also influence brand loyalty. It is recommended for companies to be able to maintain product quality, raw material quality, level of honesty in resolving consumer problems so that consumer satisfaction can be created. The ultimate goal is to increase loyalty from Uniqlo customers